QUIZIZZ ATAU KAHOOT, GAMIFIKASI DALAM PEMBELAJARAN BAHASA INGGRIS - Karmila Sari, Rita; Siti Nurani (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2021)
Gamification is the comprehensive use of game features with the aim of improving student’s performance and motivation in learning. The purpose of this present research is to conduct a systematic review of previous relevant research using the Quizizz and Kahoot! in learning English during 2021. The research method employed a Literature Study through a search on the Google Scholar page. Synthesis of literature data was analyzed from various components of students’ needs in learning English using Quizziz and Kahoot! The results point out that the online learning application Quizizz and Kahoot! have various advantages for learning English, among others, increasing the students’ ability and motivation in participating in the process of learning English actively and communicatively.